Efektivitas Eco Enzyme Limbah Jeruk Manis (Citrus sinensis) sebagai Obat Oles Penyembuhan Luka Sayat - Dzahabiyyah, Qonitah; Asy’ari, Asy’ari; Suharti, Peni (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2023)
Sweet orange (Citrus sinensis) is a fruit that is much liked by Indonesian people, but from this fruit only the flesh and skin is wasted which eventually becomes waste. Because of that, an alternative solution to this problem is needed, namely Eco Enzyme is made in the form of a multifunctional solution that is used as a wound medicine. The purpose of this study was to determine the differences in the effect of sweet orange (Citrus sinensis) Eco Enzyme concentrations on the healing rate of cuts in mice (Mus musculus). This type of research was experimental with a Completely Randomized Design (CRD) consisting of 7 treatment groups and 4 repetitions, the research data analysis technique used the Kruskal-Wallis and Mann Whitney tests. The results showed that the average percentage of healing rate by applying Eco Enzyme topical medication from sweet orange (Citrus sinensis) waste was most effective on the healing rate of cuts in mice (Mus musculus) with various concentrations, namely P5 (100%) healing rate 100% average healing time 8.25, P4 (80%) healing rate 93.75% average healing time 9.25, P3 (60%) healing rate 87.5% average healing time 9.75, P2 (40%) cure rate 81.25% average healing time 10.25, P1 (20%) healing rate 75% average healing time 10.75, positive control (K+) betadine has a healing rate of 87.5% healing time an average of 10.25, negative control (K-) distilled water has a 50% healing rate healing time beyond day 14. The conclusion obtained is that there is a difference in the effect of orange Eco Enzyme concentration sweet (Citrus sinensis) on the healing rate of cuts in mice (Mus musculus).